Kinetic and Crystallization Behaviour of Palm Oil, Palm Kernel Oil and Their Lipase-Catalyzed Interestified Blends Using Viscometry - Chen, Chit Way (2004)
The oil crystallization induction time is an important kinetic parameter that provides fundamental information in elucidating their physical and chemical properties. The main criterion for the selection of technique in determining oil induction time is sensitivity in order to apply the data into the Fisher-Turnbull model for estimation of nucleation activation fie. energy. However, most currently available techniques possessed certain limitations and drawbacks. This study investigates viscometry's potential as a new technique for oil induction time determination. Palm oil, palm kernel oil and their mixtures in different proportions were used as model systems. The catalytic nature, the efficacy and differences in chemical composition changes of the different regiospecific lipases used on the various oil substrates were also looked into. The changes in crystallization behavior of these lipase-catalyzed interesterified oils were studied by means of viscometry in complement with other techniques.In this study, lipase-catalyzed interesterification of palm oil and palm kernel oil using non-specific Pseudornonas sp. and 1,3-specific Rhizornucor miehei lipases demonstrated distinct chemical composition changes. Interesterification of palm oil tends to form more medium and long chain triacylglycerols while interesterification of palm kernel oil synthesized medium and short chain triacylglycerols. The two lipases showed high affinity in hydrolyzing palm oil fatty acids, resulting in high amounts of triacylglycerol losses and formation of partial glycerides. For palm kernel oil, the synthesis is enhanced. The hydrolysis preference of the two lipases toward palm oil acylglycerols were postulated to decrease in the order of triacylglycerol, diacylglycerol and monoacylglycerol while the opposite order is true for palm kernel oil. For the three palm oil - palm kernel oil binary blends (3:l; 1: 1 and 1:3; wlw), interesterification caused similar chemical composition changes especially on the synthesis of medium chain triacylglycerols. The lipase catalytic process was influenced by the major fiaction in the blends. Among these blends, 1:l ratio exhibited the highest degree of interesterification in terms of the total triacylglycerols concentration that increased in value while the other two blends indicated similar degrees of increment. The diversity and amount of triacylglycerols available are postulated to be the main reasons for the different catalytic activity in these binary blends. Pseudornonas sp. lipase showed higher degree and rate of interesterification compared to R. miehei lipase under all conditions. Also, differences in the regiospecificity of the two lipases did not cause different chemical composition changes to all interesterified products. However, the positional specificity and the fatty acids preference of the two lipases had effixts on the lipases' degree of interesterificatio Viscometry was an excellent and simple technique in monitoring oil crystallization process where it was able to determine the various stages of crystallization induction time. This unique capability of viscometry has merits in oil crystallization studies: correlating the phenomenon of oil fractionation (various crystallization stages) to polymorphism, polymorphic transformation and metastability of the crystal polymorphs. However, viscometry was relatively insensitive in comparison to laser polarized light anisotropy in detection of the initial nucleation event. Under isothermal cooling, palm oil and the binary blend at 3:l ratio exhibited fractionation behavior at lower temperature ranges. A two-stage crystallization process was observed where the initial stearin crystallized in the a form while olein crystallized later in the p' form. At higher isothermal temperature, no fiactionation occurred and the p' form was the only polymorph observed in a single stage crystallization process. The . transition temperature for the two-stage to a single-stage crystallization process varied with different oil compositions, indicating the effect of chemical composition on crystallization behavior. Palm kernel oil, 1 : 1 and 1 :3 blends only crystallized in a singlestage process, in the p' polymorphic form with different microstructures. The coexistence possibility of a and P' crystals and the metastability of a crystal in fat crystallization were also discussed. Interesterification using the two lipases displayed opposing effect towards crystallization behavior and nucleation rate of the two native oils. Lipase-catalyzed interesterification promoted fiactionation behavior at higher temperatures and rate in palm oil. This was not observed for palm kernel oil. Crystallization behavior changes of the 3:l and 1:3 blends confirmed our hypothesis that the two lipases showed high affinity toward the major fraction in the blend. The trend of crystallization behavior changes in the 1:l blend indicated that palm oil triacylglycerols were synthesized first before palm kernel oil. The occurrence of sequential synthesis process signified that the lipases used had higher afinity towards palm oil than palm kernel oil fatty acids. Differential scanning calorimeter thermal profiles of the various lipase-catalyzed oils were in agreement with their chemical composition and crystallization behavior changes. These thermal profiles also provided detailed information of the minor component changes that was not revealed in their crystallization behavior. The applicability of the Fisher-Turnbull model in fat and oil crystallization is discussed in the final part of this study. A review of published literatures indicated that numerous modifications and assumptions had been made to justiQ the application of this model for fats and oils nucleation. In this study, nucleation data obtained fiom laser polarized light anisotropy for the various fat systems were used to investigate those proposed modifications and assumptions. The study showed that a single slope constant might not fully represent the complex fat crystallization phenomenon as compared to multiple slope constants. The multiple slope constants established in fats nucleation may be correlated to the nucleation of compound nucleus with different triacylglycerol compositions. However, the present study also showed that application of multiple slope constants resulted in inconsistencies during calculation of the nucleation energies when statistically different induction data fiom viscometry and laser techniques were used. The results of this study thus indicate that the validity of the various modifications and assumptions made to the Fisher-Turnbull equation need further verification while the application of this model in fats and oils crystallization need further refinement.